Strategi Kepala Sekolah Sebagai Leader Dalam Meningkatkan Kepuasan Pelanggan SD Insan Terpadu Paiton Probolinggo dan Min 1 Probolinggo Melalui Customer Intimacy - Siti Halimatus Syakdiyah; Moh Romzi (CV Edujavare Publishing, 2025)
The principal as a leader has a big impact on customer satisfaction. Some institutions do not decline due to the leadership of the principal who does not provide satisfaction. As a school principal, several roles and functions can be performed and it is expected that a principal can be responsible and provide expertise to customers. Both to students, guardians, some fellow teachers, and the surrounding community. This research uses qualitative methods of case study type to understand the principal's strategy as a Leader in increasing customer satisfaction of SD Insan Terpadu Paiton Probolinggo and MIN 1 Probolinggo through Customer Intimacy. Data were obtained through interviews with principals, students, fellow teachers, observations at the research site, and document analysis, then analyzed. The results of the research are the principal's strategy as a leader in increasing customer satisfaction of SD Insan Terpadu Paiton and MIN 1 Probolinggo through customer intimacy as follows, conducting Open Communication, Active Participation, Conflict Management, Quality Education Program Development and Evaluation and Feedback.